A Systematic Review: Factors Affecting Employees’ Adoption of E-government Using an Integration of UTAUT & TTF Theories - I. A. Amrouni, Khaled; A. Arshah, Ruzaini; J. Kadi, Alaa (KnE Social Sciences, 2019)
Information and communication technologies (ICT) have been implemented mainly in government organizations, where e-government has become prevalent. The previous research focuses mostly on e-government adoption from the perspective of citizens. However, there is a scarcity of research conducted from the viewpoint of the employee. This study tried to identify and predict the factors that influence an employee to adopt technology implemented at the workplace by focusing on acceptance technology theories. The unified theory of acceptance and usage of technology (UTAUT) and Task-technology fit (TTF) using relevant findings in this review. The attempt to conduct a comprehensive explanation and analysis of the existing literature up to 2018, to understand the current situation of e-government implementation. Reviewing procedures were done by reviewing articles on e-government and related work by using indexing databases “web of science & Scopus. Finally, the results of this paper are the factors that make employees directly or indirectly adopt e-government.